2019
DOI: 10.1371/journal.pone.0224479
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of PSA-based mass screening: Evidence from a randomised controlled trial combined with register data

Abstract: In contrast to earlier studies which have used modelling to perform cost-effectiveness analysis, this study links data from a randomised controlled trial with register data from nationwide registries to reveal new evidence on costs, effectiveness, and cost-effectiveness of organised mass prostate-cancer screening based on prostate-specific antigen (PSA) testing. Cost-effectiveness analyses were conducted with individual-level data on health-care costs from comprehensive registers and register data on real-worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…We evaluated the cost-effectiveness of each strategy for three age groups with a different Pca prevalence. Several economic-based models assessed some hypothetical screening strategies based on PSA thresholds, in relation to age categories (11)(12)(13)(14)(15)(16). Our analysis, based on age and PSA stratification, try to better understand the potential impact of BP-MRI on QALY and costs.…”
Section: Procedures Comparedmentioning
confidence: 99%
“…We evaluated the cost-effectiveness of each strategy for three age groups with a different Pca prevalence. Several economic-based models assessed some hypothetical screening strategies based on PSA thresholds, in relation to age categories (11)(12)(13)(14)(15)(16). Our analysis, based on age and PSA stratification, try to better understand the potential impact of BP-MRI on QALY and costs.…”
Section: Procedures Comparedmentioning
confidence: 99%
“…62,63 There is less evidence for the cost-effectiveness of prostate cancer screening. 64 Results of one study found it would be cost-effective if offered every 4 years and only if those with low-grade cancers identified on screening were followed with active surveillance. 65 LCDs, and 2 LCDs expected to become final in early 2020.…”
Section: Cost-effectiveness Of Screeningmentioning
confidence: 99%
“…The cost-effectiveness of prostate cancer screening based on population-wide PSA testing is also uncertain, although it is known that costs of treating prostate cancer are high [ 9 ]. The Finnish Randomised Study of Screening for Prostate Cancer (FinRSPC), part of the European Randomised Study of Screening for Prostate Cancer (ERSPC) [ 10 ], followed up over 80,000 men for 20 years, but concluded that, when overall mortality was considered, neither arm could be defined as cost-effective [ 11 ]. As policy makers are interested in costs and benefits over a whole life time horizon in a screening context (particularly for prostate cancer which can take many years to manifest symptoms, if at all, during a man’s natural lifetime [ 12 ]), modelling approaches to deriving estimates of value for money are typically preferred over trial-based analyses for decision-making purposes.…”
Section: Introductionmentioning
confidence: 99%